An extended power consumption-based algorithm for communication-based applications - Enokido, Tomoya; Aikebaier, Ailixier; Takizawa, Makoto (Journal of ambient intelligence and humanized computing, 2011)
In information systems, it is critical to reduce the total electrical power consumption of computers and networks in order to realize the eco society. In our previous studies, a pair of PCB (power consumption-based) and TRB (transmission rate-based) algorithms are proposed to select one of servers so that the total power consumption of the servers is reduced for communication-based applications. In addition, the PCB algorithm is shown to be more useful for reducing the total power consumption than the TRB one. However, we consider only how much amount of electric power a server is expected to consume to transmit a file to a new requesting client in the PCB algorithm. Here, the server might be transmitting files to other clients. Therefore, we have to estimate the power consumption to transmit a file to a new client by considering how much power consumption the server would spend to transmit files to other clients. In this paper, we newly propose an extended power consumption-based (EPCB) algorithm by improving the PCB algorithm by taking into consideration how much power a server consumes to transmit files to every requesting client. In the evaluation, we show the total power consumption of servers can be more reduced by the EPCB algorithm than the PCB and TRB algorithms.